Aberrant activation of KRAS in mouse theca-interstitial cells results in female infertility - Sun, Penghao; Wang, Hongliang; Liu, Lingyun; Guo, Kaimin; Li, Xian; Cao, Yin; Ko, Chemyong; Lan, Zi-Jian; Lei, Zhenmin (Frontiers in Physiology, 2022)
KRAS plays critical roles in regulating a range of normal cellular events as well as pathological processes in many tissues mediated through a variety of signaling pathways, including ERK1/2 and AKT signaling, in a cell-, context- and development-dependent manner. The in vivo function of KRAS and its downstream targets in gonadal steroidogenic cells for the development and homeostasis of reproductive functions remain to be determined. To understand the functions of KRAS signaling in gonadal theca and interstitial cells, we generated a Kras mutant (tKrasMT) mouse line that selectively expressed a constitutively active KrasG12D in these cells. KrasG12D expression in ovarian theca cells did not block follicle development to the preovulatory stage. However, tKrasMT females failed to ovulate and thus were infertile. The phosphorylated ERK1/2 and forkhead box O1 (FOXO1) and total FOXO1 protein levels were markedly reduced in tKrasMT theca cells. KrasG12D expression in theca cells also curtailed the phosphorylation of ERK1/2 and altered the expression of several ovulation-related genes in gonadotropin-primed granulosa cells. To uncover downstream targets of KRAS/FOXO1 signaling in theca cells, we found that the expression of bone morphogenic protein 7 (Bmp7), a theca-specific factor involved in ovulation, was significantly elevated in tKrasMT theca cells. Chromosome immunoprecipitation assays demonstrated that FOXO1 interacted with the Bmp7 promoter containing forkhead response elements and that the binding activity was attenuated in tKrasMT theca cells. Moreover, Foxo1 knockdown caused an elevation, whereas Foxo1 overexpression resulted in an inhibition of Bmp7 expression, suggesting that KRAS signaling regulates FOXO1 protein levels to control Bmp7 expression in theca cells. Thus, the anovulation phenotype observed in tKrasMT mice may be attributed to aberrant KRAS/FOXO1/BMP7 signaling in theca cells. Our work provides the first in vivo evidence that maintaining normal KRAS activity in ovarian theca cells is crucial for ovulation and female fertility.